(untitled) - Baker, Donna L. (Hoboken, NJ, 2004)
Written by a Premiere Pro expert and illustrated throughout in full color, this Complete Course shows you how to master the full range of Premiere Pro tools and techniques while working on a single project. Twelve sessions and more than eighty step-by-step tutorials, accompanied by vivid color images and screen shots, walk you through the creation of a ninety-second, professional- quality video from start to finish. After completing the course, you’ll have an impressive portfolio piece and a thorough understanding of Adobe Premiere Pro fundamentals: * Use effects and transitions to change the action from scene to scene ; * Use multiple sequences to create complex nested effects ; * Use the Title Designer to create sophisticated titles.
Keywords: Motion pictures,Digital video,Phim kỹ thuật số,Ảnh động; Editing,Data processing,Editing,Data processing,Biên soạn,Xử lý dữ liệu,Biên soạn,Xử lý dữ liệu